The association between the dietary index for gut microbiota and non-alcoholic fatty liver disease and liver fibrosis: evidence from NHANES 2017–2020 - Ce Zheng; Zeming Qi; Rui Chen; Zhixiong Liao; Lanfeng Xie; Fumang Zhang (BMC Gastroenterology)
Abstract Background Imbalance in the gut microbiota is a key factor in the pathogenesis of non-alcoholic fatty liver disease (NAFLD) and liver fibrosis. The Dietary Index for Gut Microbiota (DI-GM) integrates the potential relationship between diet and gut microbiota diversity. This study aims to investigate the association between DI-GM and the risk of NAFLD and liver fibrosis, providing theoretical support for dietary intervention strategies. Methods This study utilized data from NHANES 2017–2020, including 6,181 eligible adult participants. The relationship between DI-GM and the risk of NAFLD and liver fibrosis was assessed using DI-GM quartiles, multivariate logistic regression, and restricted cubic spline (RCS) analysis. Subgroup analysis was performed to explore the predictive role of DI-GM in different populations. All analyses were weighted to ensure the representativeness of the results. Results DI-GM was negatively associated with the risks of NAFLD and liver fibrosis. As DI-GM scores increased, the risk of NAFLD and liver fibrosis significantly decreased (52.81%, 43.16%, 40.40%, and 31.98%, p < 0.05; 17.52%, 9.04%, 7.21%, and 6.78%, p < 0.05). Multivariate logistic regression analysis revealed that, in the unadjusted model (Model 1), for each unit increase in DI-GM, the risk of NAFLD decreased by 6.9% (OR = 0.931, 95% CI: 0.886–0.979, p < 0.001), while the risk of liver fibrosis decreased by 15.6% (OR = 0.844, 95% CI: 0.757–0.941, p < 0.05). In the quartile analysis, individuals in the highest DI-GM quartile (Q4) had a 58% lower risk of NAFLD compared to those in the lowest quartile (Q1) (OR = 0.42, 95% CI: 0.219–0.806, p < 0.001). The results remained significant even after adjusting for covariates. RCS analysis showed that DI-GM had a nonlinear relationship with the risks of NAFLD and liver fibrosis, with inflection points at scores of 2 and 5, indicating enhanced protective effects. Conclusion This study reveals a negative association between DI-GM and the risk of NAFLD and liver fibrosis, highlighting the potential role of healthy dietary patterns in the prevention and management of NAFLD and liver fibrosis through gut microbiota modulation, providing a theoretical basis for dietary interventions.